2016
DOI: 10.26719/2016.22.7.452
|View full text |Cite
|
Sign up to set email alerts
|

Detection of influenza B viruses with reduced sensitivity to neuraminidase inhibitor in Morocco during 2014/15 season

Abstract: We monitored phenotypic and genotypic susceptibility of influenza viruses circulating in Morocco during 2014-2015 to oseltamivir and zanamivir. Throat and nasal swab specimens were collected from outpatients (with influenza-like illness) and inpatients (with severe acute respiratory illness) and tested for influenza viruses using real-time reverse transcription polymerase chain reaction. Positive samples were inoculated in MDCK cells and virus phenotypic susceptibility to neuraminidase inhibitors (NAIs) was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…[16][17][18] In the same issue of the EMHJ, influenza outbreak characterization from other regional countries such as Jordan, lebanon, Morocco, and yemen were also published. [21][22][23][24] This is a step forward in the Eastern Mediterranean region; however, to establish effective prevention policies, more data including the health and economic burden of influenza over several seasons in the regional countries is needed.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] In the same issue of the EMHJ, influenza outbreak characterization from other regional countries such as Jordan, lebanon, Morocco, and yemen were also published. [21][22][23][24] This is a step forward in the Eastern Mediterranean region; however, to establish effective prevention policies, more data including the health and economic burden of influenza over several seasons in the regional countries is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study found that the proportion of deaths in children hospitalized with influenza attributable to influenza B virus is 1.1%, compared to 0.4% for influenza A virus (14). Finally, oseltamivir treatment seems to be less effective against influenza B viruses than against influenza A viruses (15)(16)(17), and oseltamivir-resistant mutants emerge (18)(19)(20), sometimes without a loss of fitness (21,22). Current influenza virus vaccines are an effective prophylactic countermeasure against influenza B virus infections.…”
mentioning
confidence: 99%